Implementasi Kurikulum Sekolah Alam dalam Pembentukan Pendidikan Karakter - Latifah, Alifia Nur; Muti Diah Khairani; Latifah Anjar Agustina; Isni Wahyu Nurchasanah; Safira Aulia Rahma Diani; Taufik Muhtarom (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this study is to determine how the Nature School curriculum is used to build student character. This research method is a literature study method. The literature study method is a research method used in this study. Data collection techniques are carried out by studying literature from written sources, such as books, journals, and articles to strengthen arguments. The data sources used are scientific journals with quantitative data analysis techniques. The results of the study are that the nature school curriculum does not only focus on cognitive aspects, but also on students' social, emotional, and spiritual development. In facing climate change and other environmental issues, nature-based character education is very relevant to prepare future generations. Examples of nature school activities that can shape students' character are planting trees, cleaning rivers, watering plants, gardening, raising livestock, disposing of garbage in its place, and market day activities.